Ductile polymer-based films with ultrahigh permittivity and low dielectric loss. (9th November 2017) - Zheng, Ming-Sheng; Zha, Jun-Wei; Yang, Yu; Li, Chao-Qun; Han, Peng; Hu, Chao-He; Wen, Yong-Qiang; Dang, Zhi-Min
Abstract: High-permittivity (high- k ) materials play a key role in advanced electronics and electrical power systems. How to prepare the flexible material with high permittivity and low dielectric loss turns out to be a hard work due to the essential low permittivity of polymers. In this work, a kind of ductile polymer-based composites was fabricated by incorporating ionic liquids into polymer matrices. The optimized permittivity of composite with 50 wt% ionic liquid reached up to 3.3 × 10 4, while the dielectric loss was as low as 0.65. The temperature dependence of dielectric properties was also investigated, and a high permittivity as well as low dielectric loss at 100 Hz of about 2.0 × 10 4 and 0.23 were achieved at 80 °C, respectively. Furthermore, the study reveals that the dielectric loss peaks of the composite films can be affected by the content of ionic liquid, temperature even the size of ions. In short, the finding indicates that the addition of ionic liquids into polymers provides a big opportunity to improve dielectric properties of polymer materials. Graphical abstract: Highlights: Ionic liquid/polymer composite films were produced. These polymer-based films even with high ionic liquid contents exhibited excellent ductilities. The addition of ionic liquid enhanced the permittivity of polymer matrix, while maintained a low dielectric loss. The microstructures, degrees of crystallinity, crystal forms and thermomechanical properties of films were studied.